A study of diving beetles and whirligig beetles in the river Someş (Coleoptera Dytiscoidea, Gyrinoidea) - Mathé István (Tiscia monograph series, 1999)
The authors performed a study of these coleopteran groups in the hydrographic basin of the Some? river. The material has been collected from limnocrenic. ponds, branches with stagnant water and lenthic sections of the Some? river and its affluent (upstream and downstream Ic Ponor, near the river Arinului, from "Trei lazuri", downstream Salva. downstream Beclean, upstream Rodna Veche, at Some? Odorhei, Pomi and Veti?). Al l are situated in Cluj, Bistrita-NasSud, SSlaj and Satu-Mare counties. Some data on the habitats were noted, among others their altitude, surface, depth, bottom material, vegetation, transparency and eutrophication, etc. Each species collected and determined during this expedition is presented in this paper, accompanied by some characteristic data, namely their ecological and zoogeographic character, their relative frequency and the number of Dytiscoidea and Gyrinoidea species of different altitude ranges. Some species were considered to be rare and very rare in the Romanian or Transylvanian fauna, such as Hyphydrus ovatus, Gaurodytes solieri, G. affinis, Hydaticus transversalis, Dytiscus circumflexus and D. dimidiatus.